Letter - Winstanley, E.
032-0045-001 Telegraphic Address: INLAND-"WHOLESALE, MANCHESTER." FOREIGN-"COPEXPORT, MANCHESTER." TELEPHONE: BLACKFRIARS 1212. EXTENSION NO. 87 PLEASE ADDRESS YOUR REPLY: CO-OPERATIVE WHOLESALE SOCIETY LIMITED, EXPORTERS, BUYING AND SHIPPING AGENTS. 1 . BALLOON STREET. MANCHESTER, 4. CABLE CODES A.B.C. 6TH AND 7TH EDITIONS: WESTERN UNION 8 LETTER: BENTLEY COMPLETE PHRASE: BENTLEY SECOND PHRASE: A.1. MARCONI, AND PRIVATE. Our Reference: Export.2968.ST/RN. Your Reference: HVT/EAB/DB/107. International Dept. The Trades Union Congress, Transport House, Smith Square, LONDON S.W.1. Dear Sirs, We have to inform you that our s.s. C.W.S. PROGRESS is expected to leave Garston for Rouen on Wednesday or Thursday next week, and our Steamships Department is pressing us for a complete list of the goods which are expected to come forward. This is particularly necessary, as certain packages have "been delivered to Sandon Station Liverpool, which necessitates transfer to Garston, and if you can give us some indication, even provisional, of the goods being forwarded, we shall be grateful. Thanking you in anticipation, we remain, Yours faithfully, E. Winstanley, Export Department. 292/946/32/45